Gut microbiota from sigma-1 receptor knockout mice induces depression-like behaviors and modulates the cAMP/CREB/BDNF signaling pathway - Li, Jia-Hao; Liu, Jia-Li; Li, Xiu-Wen; Liu, Yi; Yang, Jian-Zheng; Chen, Li-Jian; Zhang, Kai-Kai; Xie, Xiao-Li; Wang, Qi (Frontiers in Microbiology, 2023)
There is increasing evidence suggesting a close association between the Sigma-1 receptor (Sig-1R) and depression. However, the mechanisms through which Sig-1R exerts an antidepressant effect are not fully understood. Recently, research has suggested that the gut microbiota may play a crucial role in the development of depression. This study aimed to investigate whether the gut microbiota is involved in depression-like behaviors in mice lacking the Sigmar1 gene, and to explore the potential mechanisms involved. We found that Sig-1R deficiency led to an increase in depression-like behaviors and significant changes in gut microbiota. Antidepressant-like behaviors were restored after depletion of gut microbiota with antibiotics. The gut microbiota of Sig-1R knockout mice was sufficient to induce an increase in depression-like behaviors, which was confirmed through FMT treatment. These effects may be mediated by a reduction in neurotrophic factors through the cAMP/CREB/BDNF signaling pathway. Our study provides new insights into the mechanisms by which Sig-1R regulates depression and further supports the concept of the gut-brain axis.